The Effect of Pure Garlic (Allium Sativum L.) Juice on The Color Stability of Heat Polymerized Acrylic Resin Denture Base - Herlin Nadya Tumara; Mourent Miftahullaila; Sopan Sinamo; Yohana Aprilia Singgih; Silvia Giovani (Biomedical Journal of Indonesia, 2021)
Intoduction : PMMA or acrylic resin is a necessary material in dentistry for denture bases, one of which is often used is heat cured acrylic resin or heat polymerized acrylic resin. Garlic juice is a denture cleaner to inhibit bacteria and is also an extrinsic factor that causes discoloration. Purpose: To determine the duration of immersion in pure garlic juice which can cause discoloration of the acrylic resin. M ethods: laboratory experiments with posttest only control group design research. Results: The mean ± SD change in color of hot polymerized acrylic resin after immersing in garlic juice for 2, 4, 6, 8 hours was 0.67 ± 0.22; 0.91 ± 0.31; 1.22 ± 0.32; and 1.56 ± 0.25. Conclusion: There is an effect of soaking time with garlic juice on the base of denture acrylic resin on discoloration.